2021
DOI: 10.1016/j.bonr.2021.101068
|View full text |Cite
|
Sign up to set email alerts
|

Real-world effects and adverse events of romosozumab in Japanese osteoporotic patients: A prospective cohort study

Abstract: Real-world data on the new anti-sclerostin antibody drug, romosozumab, remain scarce. There is a strong need to accumulate and analyze data on romosozumab treatment for such conditions as osteoporosis. The purpose of this study was to investigate the therapeutic and adverse effects of romosozumab for osteoporosis treatment in clinical practice. Of the 230 osteoporosis patients prescribed romosozumab from September 2019 in this prospective multicenter cohort study, 204 patients completed 12 months of treatment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…In that study, BMD gains differed significantly in previously untreated patients, patients previously treated with bisphosphonates, or patients previously treated with denosumab; at the total hip, mean BMD gains were 5.6%, 3.3%, and 0.6%, respectively, and at the lumbar spine, mean BMD gains were 18.2%, 10.2%, and 6.4%, respectively. Similar BMD gains at the total hip and lumbar spine were also reported in another prospective real-world study in which previously untreated patients and patients previously treated with bisphosphonates or denosumab were treated with romosozumab for 12 months [ 36 ] and in a retrospective real-world study in which previously untreated patients and patients previously treated with bisphosphonates were treated with romosozumab for 12 months [ 37 ].…”
Section: Discussionsupporting
confidence: 70%
“…In that study, BMD gains differed significantly in previously untreated patients, patients previously treated with bisphosphonates, or patients previously treated with denosumab; at the total hip, mean BMD gains were 5.6%, 3.3%, and 0.6%, respectively, and at the lumbar spine, mean BMD gains were 18.2%, 10.2%, and 6.4%, respectively. Similar BMD gains at the total hip and lumbar spine were also reported in another prospective real-world study in which previously untreated patients and patients previously treated with bisphosphonates or denosumab were treated with romosozumab for 12 months [ 36 ] and in a retrospective real-world study in which previously untreated patients and patients previously treated with bisphosphonates were treated with romosozumab for 12 months [ 37 ].…”
Section: Discussionsupporting
confidence: 70%
“…These BMD‐increasing effects are generally similar to those observed in previous reports. ( 9–14 ) Thus, these results suggest that romosozumab can be recommended for patients who fit the criteria for osteoporosis with a high risk of fracture.…”
Section: Discussionmentioning
confidence: 86%
“…Because the drug has only been approved recently, there are few reports on 12‐month romosozumab treatment for patients with osteoporosis in actual clinical practice. ( 12 , 13 , 14 ) Although romosozumab has been found to be less effective in patients receiving osteoporosis medications, such as bisphosphonates, denosumab, or teriparatide, before receiving romosozumab, ( 13 , 14 , 15 ) it is still difficult to predict in which patients it will be ineffective. Therefore, this multicenter retrospective study aimed to determine the real‐world effect of romosozumab on BMD and identify factors that predict the rate of BMD increase after 12 months of romosozumab treatment.…”
Section: Introductionmentioning
confidence: 99%
“…However, in recent randomized clinical trials and metaanalyses, TPTD and abaloparatide have demonstrated increases in BMD at both trabecular and cortical sites, resulting in fracture risk reduction regardless of prior bisphosphonate treatment (16,76,80). Romosozumab following bisphosphonate therapy has demonstrated BMD gains at the LS and hip sites, although more modest than in treatment-naïve patients (81,82). A randomized trial comparing TPTD with romosozumab therapy for 12 months in postmenopausal women previously treated with bisphosphonates (mostly alendronate) for a mean period of 6 years has shown significant greater increments in BMD at the LS, TH, and FN with romosozumab than TPTD (83).…”
Section: Efficacy Of Bone-forming Agents In Treatment-naïve Patients ...mentioning
confidence: 99%